Willingness to Pay for Workplace Safety - Massimo Anelli; Felix Koenig (Institute of Labor Economics (IZA), 2021)
This paper develops a revealed-preference approach that uses budget constrain discontinuities to price workplace safety. We track hourly workers who face the decision of how many hours to work at varying levels of Covid-19 risk and leverage state-specific discontinuities in unemployment insurance eligibility criteria to identify the labor supply behavior. Results show large baseline responses at the threshold and increasing responses for higher health risks. The observed behavior implies that workers are willing to accept 34% lower incomes to reduce the fatality rate by one standard deviation, or 1% of income for a one in a million chance of dying.
Keywords: J17; J22; J28; 330; hazard pay; workplace safety; non-wage amenities; partial unemployment insurance; COVID-19; labor supply; value of life